Hochelagans and Mohawks: A Link in Iroquois History - Lighthall, W. D. (William Douw), 1857-1954 (Salt Lake City, UT : Project Gutenberg, 2005)
"Hochelagans and Mohawks: A Link in Iroquois History" by W. D. Lighthall is a historical account published in the late 19th century, specifically during the late 1800s. The book delves into the origins and historical significance of the Hochelagans and their connection to the Mohawk people within the context of Iroquois history. It explores the complexities surrounding the migratory patterns of these Indigenous groups and their interactions with other tribes and European explorers. In this detailed examination, Lighthall investigates the roots of the Hochelagan people, believed to be linked to the Huron-Iroquois family, and traces their presence in the St. Lawrence valley, particularly around Montreal. The narrative encapsulates not only the physical migrations that led to the establishment of the Mohawk and other Iroquois nations but also the cultural, political, and societal factors that influenced these transitions. Through references to explorers like Jacques Cartier and various historical accounts, Lighthall reconstructs a timeline of the Hochelagans eventual decline due to conflicts with the Hurons and Algonquins, leading to the emergence of the Mohawks as significant players in Iroquois confederacy, while posing questions about the complexities of identity and legacy in Indigenous histories. (This is an automatically generated summary.)
Release date is 2005-01-24
E-text prepared by Wallace McLean, Eric Betts, and the Project Gutenberg Online Distributed Proofreading Team from page images generously made available by the Canadian Institute for Historical Microreproductions/ Institut canadien de microreproductions historiques (Early Canadiana Online)
Keywords: Iroquois Indians; Mohawk Indians; Indians of North America -- Québec (Province) -- History